Retail FDI liberalisation and the transformation of agrifood value chains in India - Aimée Hampel-Milagrosa; Hauke Brankamp; Thomas Cremer; Alexander Haddad; Katharina Pannwitz; Franziska Wehinger; Sangeeta Agasty; Tamal Sarkar (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
In 2012, after years of heated debates, the government of India finally approved the liberalisation of foreign direct investment in retail. The landmark policy allows for 51 per cent foreign ownership in multi-brand retailing and aims to inject new businesses into the country's massive agricultural sector. Specifically, it hopes to entice multinational retailers to invest in the modernisation of the country's agricultural value chains that are notoriously intricate and plagued by a plethora of problems at various nodes. This study was conducted in the immediate aftermath of this new retail FDI policy. Evidence suggests that international retailers' response has been weak and that the expected investments have not been taking place. Various barriers at the national level continue to hinder the market penetration of modern modes of retailing; perhaps most striking is the marginal difference in governance, efficiency and profits between traditional and modern value chains. This study recommends cautiously proceeding with retail FDI liberalisation in India and accompanying it with policies that shape the process in a more inclusive manner.
Keywords: 330